Chronic Kidney Disease: Highlights for the General Pediatrician - Quigley, Raymond (Hindawi Publishing Corporation, 2012)
Chronic kidney disease in the pediatric population has been increasing. Early detection and treatment can slow down the progression of kidney disease and help prevent the development of end stage renal disease. In addition, as the kidney function declines, there are many pathophysiologic interactions with other organ systems that need to be monitored and treated. In particular, because of impaired vitamin D metabolism, calcium and phosphorus homeostasis is dysregulated and results in secondary bone disease. Anemia is common due to a number of factors including impaired erythropoietin production. Growth is often impacted by chronic kidney disease but can be improved by proper treatment. Complications of chronic kidney disease can be minimized by proper monitoring and treatment of these parameters. The general pediatrician plays a critical role in this process.